Analisis Pelaksanaan Akad Conditional Sales Purchase Agreement (CSPA) dalam Kajian Hukum Islam - Khanifa, Nurma Khusna; Hisan, Moh. Syifa’ul; Mutmainah, Kurniawati (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2023)
One of the most important teachings of the Qur'an in matters of fulfilling promises and contracts is the obligation to honor all contracts and promises, and fulfill all obligations. The Al-Qur'an also reminds that everyone will be held accountable in matters related to the promises and contracts that he does. Likewise in the Conditional Sale and Purchase Agreement (CSPA) which in Indonesian is translated as a conditional sale and purchase agreement. The method used in this research is descriptive qualitative research with the type of library research with the data source coming from literature in the form of literature. The results showed that CSPA violated one of the legal terms of the contract. Where the right to the object of the transaction is less clear. This means that ownership is not fully owned by the owner even though the promised goods have been handed over when the contract occurred. This is due to conditions, both conditions for suspending (opschortende voorwaarde) or conditions for canceling (ontbindende voorwaarde). The conclusion of this study is that CSPA is not valid in fulfilling contracts. The invalidity of the contract was caused by al-gharar (an element of harm) and al-syarthu al-fasid. So that it can be said to be vanity and does not cause any consequences.